KEPEMILIKAN ASING, TUNNELING INCENTIVE DAN INTANGIBLE ASSET TERHADAP KEPUTUSAN TRANSFER PRICING DENGAN TARIF PAJAK SEBAGAI VARIABEL INTERVENING - Lena Panca Mustika Rasa; Ina Khodijah; Cecep Abdul Hakim (LP2M Universitas Bina Bangsa, 2023)
This research is aimed to analyze the effect of foreign ownership, tunneling incentives and intangible assets on transfer pricing decisions and analyze how the effect of the tax rate variable as an intervening variable on foreign ownership, tunnelling incentives and intangible assets on transfer pricing decisions in listed consumer goods industry companies. on the Indonesia Stock Exchange (IDX) for the period 2018-2021. This research method uses quantitative methods, with saturated sampling technique, the total sample obtained in this study is 60 data from 16 companies. Secondary data is obtained from the annual financial reports published on the www.idx.go.id page. This research is processed using Smart PLS version 3.3.9. The results of the direct calculation of foreign ownership on transfer pricing have a t-statistic value of 0.652 (<1.96) and a p-value of 0.515 (>0.05). The result of calculating the direct effect of tunnelling incentive on transfer pricing has a t- statistic value of 0.258 (<1.96) and a p-value of 0.040 (<0.05). The result of calculating the direct effect of intangible assets on transfer pricing has a t-statistic value of 2.153 (<1.96) and a p-value of 1,000 (>0.05). The result of indirect effect calculation of foreign ownership through tax rates on transfer pricing has a t- statistic value of 0.247 (<1.96) and a p-value of 0.805 (>0.05). The results of the calculation of the indirect effect of tunnelling incentive through tax rates on transfer pricing have a t-statistic value of 0.534 (<1.96) and a p-value of 0.593 (>0.05) and the results of the calculation of indirect effects on intangible assets through tax rates on transfer pricing has a t-statistic value of 0.381 (<1.96) and a p-value of 0.703 (>0.05). In this study it can be concluded that foreign ownership and intangible assets have no effect on transfer pricing decisions, tunnelling incentives have no effect on transfer pricing decisions. While the tax rate is not able to be an intervening variable in the indirect relationship of foreign ownership, tunnelling incentives and intangible assets to transfer pricing decisions